Plantar pressure redistribution during running as a response to change of locomotion in triathlon - Gerych, David; Hybner, Milan; Jelen, Karel (Acta Universitatis Carolinae. Kinanthropologica, 2011)
BACKGROUND: A triathlon is a multi-sport endurance event where a change of locomotion, especially a change from biking to running, affects coordination and running efficiency. However, information about how the change of locomotion influences foot load is missing. Thus the aim of this study was to determine if the plantar pressure distribution during running changes as a consequence of change of locomotion after biking part of a triathlon race. METHODS: 10 competitive triathletes (8 male and 2 female) at age 22-46 years underwent competition simulated laboratory test which included 10min of running, 50min of cycling and 10min of running at intensities corresponding to their racing speeds. Plantar pressure at 5 segments of the foot (hindfoot, midfoot, medial forefoot, lateral forefoot, and toes) were detected during running before and after the cycling using Pedar-X Novel tensometric system. RESULTS: Maximal pressure values within entire plantar area after cycling were not significantly different. However, maximal pressure values in medial and lateral forefoot were significantly higher (p<0.05) on both feet. The maximal pressure measured on hindfoot after cycling was also higher, although, the increase was significant only on left foot (p<0.05 left, p<0.15 right). Contrary, the maximal pressure measured after cycling on toes was significantly lower on both feet (p<0.05). CONCLUSION: The results indicate a shift of footload from toes dorsally to forefoot and hindfoot during running as a consequence of fatigue resulting from previous intensive cycling. Although the results of this study revealed a significant change in plantar pressure distribution in triathletes after the bike-run transition, further research is needed to determine the effect of cycling on foot loading during running.
Keywords: financování organizované; Statistics as Topic; Movement; Pedar-X systém; plavání; statistika jako téma; pohyb; Swimming; sporty; svalová síla - dynamometr; Foot; běh; lidé; tlak; Running; Financing, Organized; noha (od hlezna dolů); biomechanika; tělesná hmotnost; oporová fáze běhu; cyklistika; Sports; tenzometrie; Body Weight; Pressure; Muscle Strength Dynamometer; Biomechanical Phenomena; Bicycling; Humans